Understanding of Islamic Business Fiqh and Accounting for Small and Medium Enterprises In Kedah Malaysia: Pemahaman Fiqih Bisnis dan Akuntansi Islam Untuk Usaha Kecil dan Menengah Di Negeri Kedah Malaysia - Zulhelmy, Zulhelmy; Senasi, Vally; Hidayat, Rizki; Hidayat, Hidayat (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
In reality, there are still small and medium business actors who do not understand Islamicjurisprudence in business and accounting. For this reason, it is important to carry out education throughoutreach to SMEs. Because doing business is a form of worship. So that the business orientation carried out isnot just about getting profit, but also fallah (luck). The writing method uses a qualitative approach with adescriptive-explanatory model. From the activities that have been carried out, small and medium businesses inKedah have received education about the concepts of business jurisprudence and accounting in Islam.Conditions were different before they took part in these activities. The understanding they gain is such as theprohibition of maysir (speculation), gharar (unclarity), usury and various other violations in muamalah, sothat they are encouraged to practice the understanding gained from the socialization that follows